2014
DOI: 10.1155/2014/707691
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines on Vaccinations in Paediatric Haematology and Oncology Patients

Abstract: Objective. Vaccinations are the most important tool to prevent infectious diseases. Chemotherapy-induced immune depression may impact the efficacy of vaccinations in children. Patients and Methods. A panel of experts of the supportive care working group of the Italian Association Paediatric Haematology Oncology (AIEOP) addressed this issue by guidelines on vaccinations in paediatric cancer patients. The literature published between 1980 and 2013 was reviewed. Results and Conclusion. During intensive chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 85 publications
(71 reference statements)
0
76
0
3
Order By: Relevance
“…In vitro studies with human T cells showed that sCTLA‐4 is a potent inhibitor of T‐cell activity, including antigen‐specific proliferation and secretion of pro‐inflammatory cytokines like IFN‐γ and IL‐17 . Tregs were also found to be able to secrete sCTLA‐4, which further contributed to the suppressive effects of the regulatory T cells by inducing secretion of immunosuppressive cytokines TGF‐β and IL‐10 . Therefore, sCTLA‐4 participates in the immune regulation in a cell‐extrinsic manner, which can affect the development and prognosis of several diseases including autoimmunity and cancer.…”
Section: Immune Checkpoint Molecules: Regulating the Immune Response mentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies with human T cells showed that sCTLA‐4 is a potent inhibitor of T‐cell activity, including antigen‐specific proliferation and secretion of pro‐inflammatory cytokines like IFN‐γ and IL‐17 . Tregs were also found to be able to secrete sCTLA‐4, which further contributed to the suppressive effects of the regulatory T cells by inducing secretion of immunosuppressive cytokines TGF‐β and IL‐10 . Therefore, sCTLA‐4 participates in the immune regulation in a cell‐extrinsic manner, which can affect the development and prognosis of several diseases including autoimmunity and cancer.…”
Section: Immune Checkpoint Molecules: Regulating the Immune Response mentioning
confidence: 99%
“…31 Tregs were also found to be able to secrete sCTLA-4, which further contributed to the suppressive effects of the regulatory T cells by inducing secretion of immunosuppressive cytokines TGF-β and IL-10. 31,32 Therefore, sCTLA-4 participates in the immune regulation in a cell-extrinsic manner, which can affect the development and prognosis of several diseases including autoimmunity and cancer.…”
Section: Soluble Isoforms Of the Ctla-4/cd28:b7 Axismentioning
confidence: 99%
“…The Italian guidelines recommend that patients who stopped the course of the vaccination schedule during chemotherapy resume the program starting from the suspended dose. It is not considered mandatory to measure antibody titers to decide on revaccination or to check response after vaccination . The British guidelines recommend giving a single dose of diphtheria‐tetanus—acellular pertussis (DTaP), inactivated poliovirus, Haemophilus influenzae b conjugate, and measles‐mumps‐rubella vaccines at 6 months after completion of standard chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Most pediatric cancer patients do recover normal immune function within 6 months of treatment completion . Furthermore, current recommendations support nonliving vaccine administration on schedule, even during chemotherapy, as long as the patient is not severely neutropenic . Ongoing research will determine the need for boosters in patients who receive vaccinations while they are immunocompromised.…”
Section: Vaccine Immunogenicity During Treatmentmentioning
confidence: 99%